The Pesher Nahum scroll from Qumran : an exegetical study of 4Q169 - Berrin, Shani L. (Studies on the Texts of the Desert of Judah, 2004)
The underlying premise of this study is the close relationship between Pesher Nahum (4Q169) and its biblical base-text. Historical and literary considerations, as well as theological, sociological, halakhic, textual, and linguistic data, are examined in terms of their exegetical functions. This edition includes a transcription and translation of 4QpNah, with textual notes. The treatment of 4QpNah follows the natural division of the extant text into five thematic literary sections, or "pericopes," each consisting of a series of "lemma/pesher units". For each pericope, proposed historical contextualizations are evaluated on the basis of exegetical criteria. "Equivalents" are "mapped" for each unit, such that individual elements of each lemma are aligned with corresponding elements from the biblical base-text. A focus upon "lemma/pesher correspondence" provides the framework for systematic exegetical analysis of 4QpNah.